FROM PRE TO POST-BMT: AUTOIMMUNITY AND VASCULITIS IN WISKOTT-ALDRICH SYNDROME. (February 2015) - Loke, Paxton; Cole, Theresa; Choo, Sharon
Abstract : Background: Wiskott-Aldrich Syndrome (WAS) is an X-linked primary immunodeficiency associated with recurrent infections, eczema, and small platelets. Patients are at risk of autoimmune complications which represent a more severe form of the WAS disease spectrum. Case history: We described a 4-year-old boy who was diagnosed with WAS, in the context of mucosal bleeding and severe thrombocytopenia. The thrombocytopenia did not respond to intravenous immunoglobulins and steroids. Several months post-diagnosis, he developed left lower lobe pneumococcal pneumonia, arthritis and a vasculitic rash which was leukocytoclastic on histology. This was followed by a rise in his IgG levels (peaking at 46 g/L), abnormal liver function tests which were predominantly cholestatic, and persistently low C4 levels. Liver biopsy showed vasculitis and autoimmune cholangitis. His anti-C1q autoantibodies and rheumatoid factor were also significantly elevated. He was treated with a combination of anti-CD20 monoclonal antibody and steroids, resulting in a significant improvement in his clinical symptoms and laboratory markers. He underwent a matched sibling bone marrow transplant (BMT) and is currently well 45 days post-transplant. Discussion: In conclusion, vasculitis in WAS requires prompt treatment due to the risk of severe morbidity and is a consideration for BMT.